Pansteatitis in African sharptooth catfish, Clarias gariepinus (Burchell), in the Kruger National Park, South Africa - Steyl, Johan Christian Abraham (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.